(untitled) (Research, Society and Development, 2020)
Studies have shown that there is a significant association between domestic dust mites and the prevalence of respiratory diseases. The objective was to present and discuss what has been published about the association between dust mites in the home environment with regard to the exacerbation of allergic and respiratory diseases. To this end, an integrative literature review was carried out between February and April 2020, according to a pre-defined protocol, with definition of eligibility criteria, to answer the question “which associations between home environment mites to allergic diseases and respiratory?”. The search for scientific articles was carried out in the SciELO and VHL databases, using the terms "mite", "asthma", "allergens" and "Respiratory diseases", with the Boolean operator "and". The main results of this review show the presence of allergens sensitizing patients in all studies, which demonstrates the existence of an association between exposure and sensitization. In this way, it makes it possible to confirm that the knowledge of allergenic components - in this case, domestic dust mites - through their identification in exams can assist in conduct beyond the treatment of the disease, also the environmental control measures in the case of patients in which there is relationship between clinical, exposure and sensitization factors.